CONSUMPTION OF DRUGS OF ABUSE DURING PREGNANCY ANALYZED BY MEANS OF THE OPPORTUNISTIC SCREENING METHOD. - Marangoni, Sônia Regina; Gavioli, Aroldo; Dias, Lashayane Eohanne; de Oliveira, Magda Lúcia Félix (Cogitare Enfermagem, 2022)
Objective: to screen drug consumption by pregnant women undergoing low-risk prenatal care and who use Primary Health Care services. Method: a cross-sectional study developed in 2016, 2018 and 2020 in a municipality from Paraná, Brazil. Consumption of drugs of abuse was screened using ASSIST 3.1. Descriptive and non-parametric statistics was used, as well as Spearman's correlation coefficient. Results: a total of 588 pregnant women were interviewed. Current use of alcohol, tobacco, marijuana and cocaine during pregnancy was verified, as well as a progressive increase in the consumption of these substances; significant correlations were found between the risk related to the consumption of drugs of abuse between them, schooling level, family income, skin color and religion. Conclusion: current consumption of one of the drugs was correlated with the others, revealing a profile of women with substance polyuse, young, primiparous, married, without their own house, medium schooling level, family income of up to two minimum wages, black- and/or brown-skinned, and catholic.